Effect of Holarrhena antidysentrica (Ha) and Andrographis paniculata (Ap) on the biofilm formation and cell membrane integrity of opportunistic pathogen Salmonella typhimurium. (December 2016) - Tanwar, Ankit; Chawla, Raman; Chakotiya, Ankita Singh; Thakur, Pallavi; Goel, Rajeev; Basu, Mitra; Arora, Rajesh; Khan, Haider Ali
Abstract: Increasing occurrence of gastroenteritis outbreaks caused by food borne opportunistic microorganisms has become a major problem in food industry as well as in immunocompromised host. Antimicrobial agents are losing their efficacy due to increase in the microbial resistance. For such reasons, conventional treatment has become limited to manage the infections state. Need of the hour is to instigate the search for safer holistic alternatives. The present study was hence conducted to assess the antibiofilm effect and mode of action of aquo alcoholic extracts of Holarrhena antidysentrica (Ha) and Andrographis paniculata (Ap) against the Salmonella enterica serovar typhimurium. Both the extracts were screened for the presence of phytocompounds followed by the characterization using Attenuated Total Reflection (ATR) infrared spectroscopy and bioactivity finger print analysis. Anti-biofilm assays were determined to test the potential of both extracts to inhibit the biofilm formation, while Propidium Iodide (PI) uptake analysis revealed that cell membrane was damaged by the exposure of nutraceuticals for 1 h. This study has demonstrated that both nutraceuticals have anti-biofilm and antimicrobial activity perturbing the membrane integrity of food-borne S. typhimurium and could be used as curative remedy to control the food borne microbial infection. Highlights: Antimicrobial resistant food borne pathogens have become an opportunistic to immunocompromised patients. Such pathogens confer resistance due to overuse of conventional treatment and also its ability to make biofilm. Holarrhena antidysenterica (Ha) and Andrographis paniculata (Ap) have been tested against Salmonella typhimurium . Both nutraceuticals could be utilized as alternative remedy to overcome the expansion of resistance to antibiotics.